The Position of Politics in the Metamorphosis of Persian Poetry and Literature - Shamaghdari, Amir Allah (2020)
The position of politics in the metamorphosis of Persian poetry and literature is the main subject of this research. In this study, politics is considered as a general term. Biographies and the history of literature each from their own view express the reasons for the growth and decline of Persian language and literature. This study aims to prove what is said so far about the causes of change and metamorphosis of Persian poetry and literature is a mere cause but can be considered as one of the reasons for the metamorphosis of poetry style. The authors of this article believe that the political, social, religious, cultural, economic, historical, regional and environmental factors and other reasons have affected the metamorphosis of Persian poetry and literature. The authors consider the results of the past review of Persian literature as a necessity to draw a future map and to encourage the scholars and thinkers for innovative, attractive, creative and compatible planning with the new conditions of the today world. Considering the cyberspace and social networks is another point in this study which emphasized the importance of applying these kinds of inclusive technologies in Persian language and literature promotion